2021
DOI: 10.1038/s41467-021-21017-6
|View full text |Cite
|
Sign up to set email alerts
|

Alloying–realloying enabled high durability for Pt–Pd-3d-transition metal nanoparticle fuel cell catalysts

Abstract: Alloying noble metals with non-noble metals enables high activity while reducing the cost of electrocatalysts in fuel cells. However, under fuel cell operating conditions, state-of-the-art oxygen reduction reaction alloy catalysts either feature high atomic percentages of noble metals (>70%) with limited durability or show poor durability when lower percentages of noble metals (<50%) are used. Here, we demonstrate a highly-durable alloy catalyst derived by alloying PtPd (<50%) with 3d-transition metal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
130
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 165 publications
(146 citation statements)
references
References 56 publications
3
130
0
Order By: Relevance
“…Recently, a PtPdCu ternary oxygen reduction reaction electrocatalyst has been proved to be active and stable in the acidic media due to realloying. [44] This agrees well with our experimental observations showing limited amount of Co leaching after the durability test in acidic electrolyte and demonstrates great promise of nano-alloy electrocatalysts in acidic media.…”
Section: Angewandte Chemiesupporting
confidence: 91%
“…Recently, a PtPdCu ternary oxygen reduction reaction electrocatalyst has been proved to be active and stable in the acidic media due to realloying. [44] This agrees well with our experimental observations showing limited amount of Co leaching after the durability test in acidic electrolyte and demonstrates great promise of nano-alloy electrocatalysts in acidic media.…”
Section: Angewandte Chemiesupporting
confidence: 91%
“…As promising catalysts in heterogeneous catalysis, HEAs generally consist of five or more metals, which display the structure-dependent synergistic effects and enhanced catalytic performance in terms of activity and durability 13 , 14 . Moreover, since the HEAs can largely decrease the usage of noble metals and thus reduce the cost of catalyst 15 , they have been attracted increasing research interests. For instance, Li et al 16 reported a small HEAs Pt 18 Ni 26 Fe 15 Co 14 Cu 27 nanoparticles (NPs) with a mean size of ~3.4 nm as an efficient catalyst for alkaline methanol oxidation reaction, on which the synergistic effects facilitate the site-to-site electron transfer during both reduction and oxidation processes.…”
Section: Introductionmentioning
confidence: 99%
“…It is the role of catalysis in electrolysis water-splitting cells that is the focal point of this review. The readers are referred to several recent reviews for the role of catalysis in fuel cells [15,[19][20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%